Biotechnology in functional foods and nutraceuticals - Bagchi, Debasis, 1954-; Lau, Francis (Francis C.); Ghosh, Dilip K. (CRC Press, 2010)
Modern food biotechnology is now a billion-dollar industry, producing functional foods and nutraceuticals that offer a whole host of increased health benefits. This book begins with an overview of the advances in biotechnology and their contributions to food science. It then examines the impact of genetic modification on functional foods.